ANALISIS FAKTOR-FAKTOR YANG MENYEBABKAN KREDIT MACET PADA CREDIT UNION MUARE PESISIR KANTOR PELAYANAN SIANTAN - Wahyuni, Lela (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem in this research is â€œthe cause of non performed loans at credit union Muare Pesisir service office Siantan ?â€. The research method used is descriptive qualitative method with the form of survey research. A conclusion that has acquired after do this research is The causes of stuck credit from the cu not thorough to analyse credit provision and provides credit to members who do not qualify because of the familial relationship. The causes of non-performing loans derived from the members is an effort from a member of decline , the abuse credit , we new loans and the members beritikad not good. Non-performing loans of the large the ratio last three years in cu muare coastal center siantan 2014 which 6.5 % , in 2015 of 6.3 % and on 2016 of 3.18 % . The ratio of non-performing loans of the highest was in 2014 and 2015 where the number was exceeding the limit of a maximum of which is the ratio of non-performing loans of the 5 percent that shows cu was not healthy .And occurring credit repair on 2016 signifying the ratio its on 2016 decreased to 3.18 % . Keywords: Credit union, Non Performing Loans FactorsÂ